Asymmetric Market Reactions To Sukuk Issuance - Syazwani Abd Rahim; Nursilah Ahmad (Novelty Journals, 2024)
The main aim of this study is to investigate whether market reacts asymmetrically to the issuance of selected Sukuk in Malaysia for the period 2009-2011. 45 companies are selected and data on the date of issuance, issuers, issue size in million and tenors in years for each group are collected from the Securities Commission Malaysia (SC) and Bloomberg database. The study employs event study methodology using cumulative average abnormal return (CAAR) on all symmetric and asymmetric events of [0,0] 1-day, [-1,+1] 3-day, [-2, +2] 5-day, [-5,+5] 11-day, [-1,+2] 4-day, [-2,+1] 4-day, [-2,+5] 8-day, [-5,+2] 8-day, [-15,+5] 21-day, [-5,+30] 36-day, [-30,+60] 91-day, [-60,+30] 91-day and [-90,+15] 106-day based on the reaction of the FTSE Hijrah Shari’ah Index and Dow Jones Islamic Market Index (DJIM) to the announcement of Sukuk issuance. The findings would be useful to Sukuk issuers and decision-makers to ensure the stability of the Islamic capital market and sustainable economic growth.